Hypercalcemia in pregnancy - Cano Bautista, Luisa Fernanda (2024)
Hyperparathyroidism during pregnancy is not a frequent diagnosis and is generally adiagnosis of exclusion. It may present with emetic episodes, alteration of the mentalsphere and of the state of consciousness, and abdominal pain. This causes difficultiesin its initial diagnosis and delay in starting treatment that leads to complicationssuch as gestational loss. The case presented is of a 30-year-old pregnant woman of8.5 weeks, with no known history of chronic hypertension, who was admitted withneurological symptoms associated with persistent hyperemesis, polyarthralgia andhypertensive crisis. Autoimmune disease was ruled out. She had normal vitaminlevels, with evidence of altered renal function, hypercalcemia and calciuria, renalultrasound with nephrocalcinosis and thyroid ultrasound with apparent parathyroidmass. She showed a torpid neurological evolution. The diagnosis was primaryhyperparathyroidism with high obstetric risk, requiring termination of pregnancyand resection of the parathyroid lesion. Symptomatology, renal function and calciumlevels improved. Primary hyperparathyroidism is not a frequent etiology in pregnantwomen, being more a diagnosis of exclusion, with a wide spectrum in its clinicalpresentation.